MENDELEY APPLICATION TRAINING TO IMPROVE STUDENT FINAL ASSIGNMENT WRITING - Thamrin, Lily; Veronica, Tjen; Suhardi, Suhardi; Lusi, Lusi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Every student who has entered the final study period must complete the final project/thesis as a graduation requirement. In order to produce quality and responsible writing, students must have the provision of knowledge and how to find, find and determine the correct references and write good citations to avoid plagiarism in thesis writing. The Mendeley application can assist in managing reference sources and writing citations, which can synchronize with the references menu in Microsoft Word. So the PKM team of the Mandarin Language Education Study Program, FKIP UNTAN, provided training on using the Mendeley Application to 20 semester VII students taking thesis writing. Based on the results of the training activities, it can see that 95% of the students who attended the training were able to master the Mendeley application. The obstacle faced in this training was the problem of student laptop devices still using a low version of the Windows operating system, resulting in students needing help installing the Mendeley application. However, this obstacle can be handled thanks to the direction and guidance of the lecturer in the PKM Team. The Mendeley application is relatively easy to learn, understand, and operate, so students will use the Mendeley application as support in completing their final project/thesis.